Rapid synthesis method of sulfate intercalation catalyst for seawater electrolysis hydrogen production

The preparation of CoFe LDH catalyst in seawater electrolysis by electrodeposition-oxidation method solves the problems of high cost and poor corrosion resistance of existing catalysts, and achieves efficient and stable hydrogen production by seawater electrolysis, with low cost and high stability.

CN119615258AActive Publication Date: 2025-03-14HARBIN INST OF TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411799780.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-14
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

Existing non-precious metal catalysts have problems such as high cost, poor corrosion resistance and difficult industrial application in seawater electrolysis, making it difficult to achieve high OER catalytic activity and stability.

Method used

The CoFe LDH structure was formed on the substrate surface by electrodeposition-oxidation method, and the catalytic activity was regulated by the sulfate between the layers and inhibited Co3+ dissolution, and a sulfate intercalation catalyst was prepared.

Benefits of technology

It achieves an overpotential of only 265mV in natural seawater with current density of 100mA·cm-2, and maintains a low attenuation rate after continuous electrolysis for 1000 hours, with low cost, high stability and excellent catalytic activity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615258A_ABST
    Figure CN119615258A_ABST
Patent Text Reader

Abstract

The invention discloses a rapid synthesis method of a sulfate intercalation catalyst for seawater electrolysis hydrogen production, and the method comprises the following steps: 1, dissolving a metal salt in a solvent to obtain an initial deposition solution, and dissolving a stabilizer in the initial deposition solution to obtain an electro-deposition solution; 2, placing the substrate in an electro-deposition solution, and carrying out electro-deposition to obtain a CoFe catalyst precursor; 3, placing the CoFe catalyst precursor in a mixed solution of thiourea and potassium hydroxide for oxidation; and 4, placing the oxidized catalyst in a potassium hydroxide solution for cyclic oxidation. The preparation method disclosed by the invention is simple, rapid and efficient, and can be suitable for preparing a large-area electrode, the activated electrode has excellent OER activity and extremely strong chlorine resistance, only 265 mV overpotential is needed when the current density in natural seawater reaches 100 mA. Cm <-2 >, and only 5.0 mu V / h low attenuation rate appears after continuous electrolysis is performed for 1000 hours in the natural seawater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of high-salt water hydrogen energy catalysis and relates to a method for preparing a non-precious metal catalyst, and specifically relates to a method for quickly preparing a highly efficient and stable sulfate intercalation catalyst for producing hydrogen by electrolyzing seawater. Background Art

[0002] The world's growing concern about serious environmental problems and energy crises has driven the development of renewable clean energy, especially hydrogen energy, solar energy and wind energy. Among them, hydrogen energy is considered to be a superior alternative to traditional fuels due to its unique pollution-free, high energy density and wide range of sources. Hydrogen energy can be obtained through coal and biomass pyrolysis, natural gas reforming and water electrolysis. Among them, hydrogen production based on water electrolysis is considered to be the most efficient and cleanest method of hydrogen production. However, water electrolysis requires a large amount of pure water. Combined with the growing demand for energy, water electrolysis will further increase water consumption in the future, exacerbating the "water shortage" on the earth. Seawater accounts for about 97% of the water resources on the earth. Using seawater electrolysis to produce hydrogen can directly alleviate the competition for water resources between life and the hydrogen production industry.

[0003] The electrolysis reaction of water consists of two half reactions: oxygen evolution reaction (OER) at the anode and hydrogen evolution reaction (HER) at the cathode. The energy consumption of the anode accounts for more than 90% of the energy consumption of the electrolysis reaction. However, the impurity ions Cl in seawater - It is also very easy to be oxidized at the anode, and chlorine evolution reaction (CER) occurs, which not only increases the energy consumption of the anode, but also causes corrosion of the anode. Although there is a theoretical potential difference of 0.48V between CER and OER, the potential difference between OER and CER is further shortened due to the poor OER activity of the actual catalyst, which limits its stable hydrogen production under high current.

[0004] CN117468043A discloses a single-atom Ir loaded on NiFe LDH type catalyst. The dispersed Ir provides more catalytic active sites and significantly improves the OER activity. However, the catalyst contains precious metal Ir, which leads to a high cost of the catalyst, making it difficult to achieve industrial application. CN117385405A discloses a method for densely coating NiFe LDH on the surface of NF to avoid direct contact between the NF skeleton and Cl - Contact, thereby inhibiting Cl corrosion. However, its stability is only at 400mA·cm -2The current density can be maintained for 250 hours, which is far from meeting the requirements of electrode stability for industrial water electrolysis. CN117187855A discloses a method for synthesizing NiFe LDH with rapid surface reconstruction, which synthesizes CV-B-NiFeLDH by hydrothermal, boron modification and cyclic voltammetry. The material can achieve electrolysis of 100mA·cm in natural seawater. -2 The current density only requires an overpotential of 219 mV and exhibits excellent reaction kinetics (53.5 mV·dec -1 ). However, this synthesis method is complicated and requires the introduction of additional boron, which makes this method unsuitable for the synthesis of large-area electrodes.

[0005] Currently available non-precious metal catalysts have obvious problems such as high cost, poor corrosion resistance and high difficulty in industrial application, making them difficult to be directly applied to seawater electrolysis. Therefore, it is crucial to develop a new catalyst that achieves high OER catalytic activity, high selectivity and strong corrosion resistance for direct seawater electrolysis. Summary of the invention

[0006] The purpose of the present invention is to provide a rapid synthesis method of a sulfate intercalation catalyst for electrolysis of seawater to produce hydrogen. In this method, CoFe is grown on the surface of a substrate by an electrodeposition-oxidation method and further oxidized to form a sulfate intercalated CoFe LDH structure, so as to obtain a high-performance seawater direct electrolysis oxygen decomposition catalyst with a specific structure, and the interlayer sulfate is used to regulate the catalytic activity of CoFe LDH and inhibit the oxidation of Co 3+ The preparation method of the present invention is simple, fast and efficient, and can be applied to the preparation of large-area electrodes. The activated electrode has excellent OER activity and strong chlorine resistance, and the current density in natural seawater reaches 100 mA cm -2 Only 265mV overpotential is required, and after 1000h of continuous electrolysis in natural seawater, a low decay rate of only 5.0μV / h occurs. At the same time, the catalyst has the advantages of low synthesis cost, high stability and good catalytic activity, providing a new material research and development idea for hydrogen production by seawater electrolysis.

[0007] The objective of the present invention is achieved through the following technical solutions:

[0008] A rapid synthesis method of a sulfate intercalation catalyst for producing hydrogen by electrolysis of seawater, specifically comprising the following steps:

[0009] Step 1: dissolving a metal salt in a solvent to obtain an initial deposition solution, and then slowly dissolving a stabilizer in the initial deposition solution to obtain an electrodeposition solution, wherein:

[0010] The metal salts are cobalt salts and iron salts;

[0011] The cobalt salt is one of cobalt chloride, cobalt sulfate or cobalt nitrate, and the concentration is 0.15 to 0.25 mol / L, for example, 0.15 mol / L, 0.18 mol / L, 0.20 mol / L, 0.23 mol / L and 0.25 mol / L, but is not limited to the listed concentrations, and other concentrations not listed within the concentration range are also applicable;

[0012] The iron salt is one of ferrous chloride and ferrous sulfate, and the concentration is 0.03-0.08 mol / L, for example, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L, 0.06 mol / L, 0.07 mol / L and 0.08 mol / L, but is not limited to the listed concentrations, and other concentrations not listed within the concentration range are also applicable;

[0013] The solvent is deionized water;

[0014] The stabilizer is any combination of one or more of ammonium chloride, boric acid and sodium citrate, and typical but non-limiting combinations include a combination of boric acid and ammonium chloride, and a combination of ammonium chloride and sodium citrate;

[0015] The concentration of the stabilizer is 0.2-0.5 mol / L, for example, 0.20 mol / L, 0.30 mol / L, 0.40 mol / L, 0.50 mol / L, but is not limited to the listed concentrations, and other concentrations not listed within the concentration range are also applicable;

[0016] Step 2: placing the substrate in an electrodeposition solution for electrodeposition, and then washing and drying to remove residual ions on the surface to obtain a CoFe catalyst precursor, wherein:

[0017] The substrate is one of foamed nickel and Raney nickel mesh;

[0018] The electrodeposition time is 10 to 20 minutes, and the deposition current is 60 mA / cm 2 Pulse current, temperature is 40-60°C, for example, 40°C, 45°C, 50°C, 55°C and 60°C, but is not limited to the listed temperatures, and other temperatures not listed within the concentration range are also applicable;

[0019] The washing reagents should include one or two of anhydrous ethanol and deionized water, but at least deionized water, and the drying method is vacuum drying or freeze drying;

[0020] Step 3: placing the CoFe catalyst precursor in a mixed solution of thiourea and potassium hydroxide for oxidation, wherein:

[0021] In the mixed solution of thiourea and potassium hydroxide, the concentration of potassium hydroxide is 1.0 mol / L, and the concentration of thiourea is 0.03-0.05 mol / L. For example, the concentration of thiourea can be 0.03 mol / L, 0.04 mol / L, or 0.05 mol / L, but is not limited to the concentrations listed. Other concentrations not listed within the concentration range are also applicable.

[0022] In the mixed solution of thiourea and potassium hydroxide, the solvent is deionized water;

[0023] The current intensity of the oxidation is 200-250 mA·cm -2 , but is not limited to the current densities listed, and other current densities not listed within the range are also applicable;

[0024] The oxidation time is 3 to 5 minutes, but is not limited to the listed oxidation time, and other oxidation times not listed within the range are also applicable;

[0025] Step 4: placing the oxidized catalyst in a potassium hydroxide solution for cyclic oxidation to obtain a sulfate intercalation catalyst, wherein:

[0026] The concentration of the potassium hydroxide solution is 1.0 mol / L;

[0027] In the potassium hydroxide solution, the solvent is deionized water;

[0028] The potential range of the cyclic oxidation is 0.2-0.7 V, and the rate is 5 mV·s -1 ;

[0029] The number of cyclic oxidations is 40 to 50 times, for example, 40 times, 45 times, or 50 times, but is not limited to the listed oxidation times, and other oxidation times not listed within the range are also applicable.

[0030] The catalyst prepared by the above method can be used for direct electrolysis of seawater to produce hydrogen, and the surface of the catalyst is evenly distributed with cobalt, iron and sulfur elements. The oxygen evolution reaction (OER) is a typical four-electron reaction, which undergoes OH - →OH * →O * →OOH * →O2, the theoretical potential is 1.23V. However, due to the strong or weak adsorption of reaction intermediates, the actual OER potential is often higher than 1.23V. The unfilled d orbital of cobalt gives it a better adsorption strength for reaction intermediates, thus showing a stronger catalytic activity. In addition, studies have shown that Fe doping can effectively regulate the adsorption strength. NiFe LDH has been proven to be the most effective OER catalyst, and its catalytic activity is much better than commercial RuO2. Secondly, anions can effectively regulate the catalytic activity of LDH, especially SO42- and PO4 3- Therefore, the present invention deposits cobalt and iron to form CoFe, and further converts SO4 2- It is activated synchronously with CoFe LDH to form sulfate intercalated CoFe LDH, thereby constructing an efficient and stable catalyst for direct electrolysis of seawater to produce hydrogen.

[0031] Compared with the prior art, the present invention has the following advantages:

[0032] 1. The preparation method of the catalyst of the present invention has a simple process, low operation difficulty, low equipment requirements and is easy to prepare large-area electrodes.

[0033] 2. In the preparation process of the present invention, CoFe LDH and SO4 are reacted by electrodeposition and oxidation. 2- Synchronously activated, and formed a specific intercalation structure (SO4 2- / CoFe LDH).

[0034] 3. SO4 synthesized by the present invention 2- / CoFe LDH has obvious nanosheet structure, and SAED diffraction proves SO4 2- The CoFe LDH layer is inserted and the interlayer spacing is increased. Experimental results show that the catalyst of the present invention has a low voltage and excellent catalytic activity in the direct electrolysis of seawater to produce hydrogen. The voltage reaches 100 mA cm in natural seawater. -2 The current density only requires 265mV overpotential, and 500mA·cm -2 After running for 1000 hours at industrial-level current, the catalyst decay rate was only 5μV / h.

[0035] 4. The materials required for the synthesis of the catalyst in the present invention are cheap and easy to obtain, and have the advantages of low preparation cost, low electrolysis energy consumption and high stability. It has broad application prospects in the fields of marine wind power consumption to produce green hydrogen and high-salt wastewater treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 is the SEM image of the catalyst in Example 1;

[0037] Figure 2 TEM image of the catalyst in Example 1;

[0038] Figure 3 is the LSV curve of the catalyst in Example 1;

[0039] Figure 4 is the LSV curve of the full hydrolysis performance of the catalyst in Example 1;

[0040] Figure 5is the voltage curve under constant current for direct electrolysis of seawater in Example 1;

[0041] Figure 6 TEM image of the catalyst after stability test in Example 1;

[0042] Figure 7 This is the Faraday efficiency test diagram in Example 1;

[0043] Figure 8 is the LSV curve of the catalyst before and after the stability test in Example 1;

[0044] Fig. 9 is the LSV curve of the catalyst in Example 2;

[0045] Fig.10 This is the LSV curve of the catalyst in Example 3. DETAILED DESCRIPTION

[0046] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0047] Example 1

[0048] This example prepares the sulfate intercalation catalyst according to the following steps:

[0049] Step 1: Dissolve CoSO4 and FeSO4 in deionized water to obtain an initial deposition solution, and then slowly dissolve ammonium chloride and boric acid in the initial deposition solution to obtain an electrodeposition solution. The electrodeposition solution includes 0.15 mol / L CoCl2, 0.03 mol / L FeSO4, 0.2 mol / L NH4Cl and 0.2 mol / L H3BO3.

[0050] Step 2: Immerse the nickel foam in the electrodeposition solution and -2 The deposition was carried out for 10 min at a current density of 400 nm.

[0051] Step 3: Wash with anhydrous ethanol and deionized water respectively, and obtain a catalyst precursor by vacuum drying.

[0052] Step 4: The catalyst precursor was placed in a 0.03 mol / L thiourea and 1.0 mol / L potassium hydroxide solution at 200 mA cm -2 The current was oxidized for 3 min.

[0053] Step 5: The oxidized catalyst is placed in a 1.0 mol / L potassium hydroxide solution at an oxidation potential of 5 mV·s in the range of 0.2 to 0.7 V.-1 The catalyst was obtained by cyclic oxidation 40 times at a rate of.

[0054] The catalyst was characterized by SEM and TEM tests. Figure 1 and Figure 2 As shown. Figure 1 It can be seen that nanosheet structures grow on the catalyst surface; Figure 2 It can be seen that SO4 2- Successfully inserted into the interlayer of CoFe LDH to form an intercalated structure.

[0055] The catalyst was tested for OER performance in the following manner: an electrolyte containing real seawater and 1.0 mol / L KOH was poured into a single-chamber electrolyzer and tested under a three-electrode system, with the catalyst prepared in this example as the working electrode, the platinum sheet as the counter electrode, and Hg / HgO as the reference electrode. The performance of the catalyst was evaluated by linear sweep voltammetry, and the test results are shown in FIG. Figure 3 As shown. Figure 3 It can be seen that when the current density reaches 100 mA cm -2 The overpotential is only 265mV.

[0056] The catalyst was tested for its water splitting performance. The test method was as follows: Pt / C / NF electrode was used as counter electrode and the catalyst prepared in this example was used as working electrode. The performance of the catalytic system was evaluated by linear sweep voltammetry. The test results were as follows: Figure 4 The preparation method of Pt / C / NF electrode is as follows: 30 mg Pt / C is dissolved in a mixed solvent consisting of 30 μL and 200 μL, and then the mixture is coated on the cleaned nickel foam after ultrasonic mixing for 30 minutes, and finally vacuum dried at 60°C for 30 minutes. Figure 4 It can be seen that when the current density reaches 100 mA cm -2 The voltage is only 1.682V.

[0057] The stability of the catalyst was tested as follows: seawater containing 1 mol / L potassium hydroxide was poured into a single-chamber electrolyzer, the catalyst prepared in this example was used as the working electrode, and Pt / C / NF was used as the counter electrode. -2 Electrolysis was performed under constant current, and the cell voltage data obtained were as follows: Figure 5 After the test, the catalyst was subjected to SEM characterization test, and the results were as follows Figure 6 The Faraday efficiency of the electrode is Figure 7 As shown in Figure 2, the OER performance of the catalyst before and after 1000h testing is shown in Figure 2. Figure 8 As shown. Figures 5 to 8 It can be seen that SO4 2- / CoFe LDH can achieve 1000h stable seawater electrolysis hydrogen production, and almost 100% OER selectivity can be achieved during the electrolysis process. After a thousand hours of testing, the nanosheet structure on the electrode surface is maintained, and the performance decay rate is less than 5μV / h.

[0058] Example 2

[0059] This example prepares the sulfate intercalation catalyst according to the following steps:

[0060] Step 1: Dissolve CoCl2 and FeCl2 in deionized water to obtain an initial deposition solution, and then slowly dissolve ammonium chloride and sodium citrate in the initial deposition solution to obtain an electrodeposition solution. The electrodeposition solution includes 0.15 mol / L CoCl2, 0.03 mol / L FeSO4, 0.5 mol / L NH4Cl and 0.5 mol / L sodium citrate.

[0061] Step 2: Immerse the Raney nickel mesh in the electrodeposition solution and -2 The deposition was carried out for 20 min at a current density of 400 nm.

[0062] Step 3: Wash with anhydrous ethanol and deionized water respectively, and obtain a catalyst precursor by freeze-drying.

[0063] Step 4: The catalyst precursor was placed in a 0.05 mol / L thiourea and 1.0 mol / L potassium hydroxide solution at 250 mA cm -2 The current was oxidized for 5 min.

[0064] Step 5: The oxidized catalyst is placed in a 1.0 mol / L potassium hydroxide solution at an oxidation potential of 5 mV·s in the range of 0.2 to 0.7 V. -1 The catalyst was obtained by cyclic oxidation 50 times at a rate of.

[0065] The catalyst prepared in this example was tested for OER performance, and the test results are as follows: Fig. 9 As shown. Fig. 9 It can be seen that when the current density reaches 100 mA cm -2 The overpotential is only 274mV.

[0066] Example 3

[0067] This example prepares the sulfate intercalation catalyst according to the following steps:

[0068] Step 1: Dissolve Co(NO3)2 and FeCl2 in deionized water to obtain an initial deposition solution, and then slowly dissolve ammonium chloride and sodium citrate in the initial deposition solution to obtain an electrodeposition solution. The electrodeposition solution includes 0.20 mol / L Co(NO3)2, 0.04 mol / L FeSO4, 0.4 mol / L NH4Cl and 0.4 mol / L sodium citrate.

[0069] Step 2: Immerse the nickel foam in the electrodeposition solution and -2 The deposition was carried out for 15 min at a current density of 400 nm.

[0070] Step 3: Wash with anhydrous ethanol and deionized water respectively, and obtain a catalyst precursor by freeze-drying.

[0071] Step 4: The catalyst precursor was placed in a 0.04 mol / L thiourea and 1.0 mol / L potassium hydroxide solution at 230 mA cm -2 The current was oxidized for 4 min.

[0072] Step 5: The oxidized catalyst is placed in a 1.0 mol / L potassium hydroxide solution at an oxidation potential of 5 mV·s in the range of 0.2 to 0.7 V. -1 The catalyst was obtained by cyclic oxidation for 45 times at a rate of.

[0073] The catalyst prepared in this example was tested for OER performance, and the test results are as follows: Fig.10 As shown. Fig.10 It can be seen that when the current density reaches 100 mA cm -2 The overpotential is only 268mV.

Claims

1. A rapid synthesis method of a sulfate intercalation catalyst for hydrogen production by electrolysis of seawater, characterized in that The method comprises the following steps: Step 1, dissolving a metal salt in a solvent to obtain an initial deposition solution, and then slowly dissolving a stabilizer in the initial deposition solution to obtain an electrodeposition solution, wherein: the metal salt is a cobalt salt and an iron salt, the concentration of the cobalt salt is 0.15-0.25 mol / L, the concentration of the iron salt is 0.03-0.08 mol / L; the concentration of the stabilizer is 0.2-0.5 mol / L; Step 2: placing the substrate in an electrodeposition solution for electrodeposition, then washing and drying to obtain a CoFe catalyst precursor, wherein: the electrodeposition time is 10 to 20 minutes, and the deposition current is 60 mA / cm 2 Pulse current, temperature is 40~60℃; Step 3: Place the CoFe catalyst precursor in a mixed solution of thiourea and potassium hydroxide for oxidation, wherein the oxidation current intensity is 200-250 mA cm -2 , time is 3 to 5 minutes; Step 4: placing the oxidized catalyst in a potassium hydroxide solution for cyclic oxidation to obtain a sulfate intercalation catalyst, wherein: the potential range of the cyclic oxidation is 0.2-0.7V, and the rate is 5mV·s -1 , 40 to 50 times.

2. The rapid synthesis method of sulfate intercalation catalyst for hydrogen production by electrolysis of seawater according to claim 1, characterized in that In the step 1, the cobalt salt is one of cobalt chloride, cobalt sulfate or cobalt nitrate, the iron salt is one of ferrous chloride and ferrous sulfate, the stabilizer is one or more of ammonium chloride, boric acid and sodium citrate in any combination, and the solvent is deionized water.

3. The rapid synthesis method of sulfate intercalation catalyst for hydrogen production by electrolysis of seawater according to claim 2, characterized in that The stabilizer is one of a combination of boric acid and ammonium chloride and a combination of ammonium chloride and sodium citrate.

4. The rapid synthesis method of sulfate intercalation catalyst for hydrogen production by electrolysis of seawater according to claim 1, characterized in that In the step 2, the substrate is one of foamed nickel and Raney nickel mesh.

5. The rapid synthesis method of sulfate intercalation catalyst for hydrogen production by electrolysis of seawater according to claim 1, characterized in that In the step 2, the reagents used for washing include one or both of anhydrous ethanol and deionized water, and the drying method is vacuum drying or freeze drying.

6. The rapid synthesis method of sulfate intercalation catalyst for hydrogen production by electrolysis of seawater according to claim 1, characterized in that In the step 3, in the mixed solution of thiourea and potassium hydroxide, the concentration of potassium hydroxide is 1.0 mol / L, the concentration of thiourea is 0.03-0.05 mol / L, and the solvent is deionized water.

7. The rapid synthesis method of sulfate intercalation catalyst for hydrogen production by electrolysis of seawater according to claim 1, characterized in that In the step 4, the concentration of the potassium hydroxide solution is 1.0 mol / L, and the solvent is deionized water.

8. A sulfate intercalation catalyst synthesized by the method according to any one of claims 1 to 7.

9. Use of a sulfate intercalation catalyst synthesized by the method according to any one of claims 1 to 7 in direct electrolysis of seawater to produce hydrogen.

Citation Information

Patent Citations

  • Seawater hydrogen production electrode and preparation method and application thereof

    CN115821283A

  • Method for preparing NiFe-LDH nanosheet efficient oxygen evolution catalyst through surface reconstruction

    CN117187855A

  • Preparation method of high-stability NiFe-LDH oxygen evolution catalyst and application of high-stability NiFe-LDH oxygen evolution catalyst in seawater hydrogen production

    CN117385405A

  • Preparation method of Ir monatomic modified NiFe LDH nanosheet oxygen evolution catalyst

    CN117468043A

  • Intercalated hydrotalcite catalyst as well as preparation method and application thereof

    CN117983256A